Indonesia and Malaysia Fiscal Policy Stimulus in the Era of the Covid-19 Pandemic - Mustofa Mustofa; Aula Ahmad Hafidh Saiful Fikri; Nita Kusumawardani; Muhammad Roestam Afandi (Budapest International Research and Critics University, 2022)
This study aims to analyze policy stimulus fiscal policy in Indonesia and Malaysia to anticipate the impact of the resulting economy from the Covid-19 pandemic. Study this is study descriptive. Source of data obtained from secondary data, documents, and relevant literature. Based on the results of the study literature The COVID-19 pandemic has an impact significant on the performance sector economy especially group-related business activity tourist like sector provision of accommodation eat drink, as well transportation and warehousing. Fiscal stimulus packages issued by the countries of Indonesia and Malaysia can be categorized as three goals, namely the stimulus for resolving crisis health society, a stimulus for destination consumption (side demand), and a stimulus for destination production (side offer). The vaccination program in Malaysia has achieved more targets fast than the vaccination program in Indonesia. Economic performance growth is positive in 2021 and 2022 for Indonesia and Malaysia.